2022
DOI: 10.3389/fphar.2022.884170
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Binge Alcohol Enhances Early Alzheimer’s Disease Pathology in Adulthood Through Proinflammatory Neuroimmune Activation

Abstract: Epidemiological studies suggest that heavy alcohol use early in life is associated with increased risk for Alzheimer’s disease (AD). However, mechanisms connecting AD with alcohol use have not been identified. Both heavy alcohol use and AD feature increased proinflammatory signaling. Therefore, we hypothesized that adolescent binge ethanol would increase AD molecular and behavioral pathology in adulthood through proinflammatory signaling. The 3xTg-AD mouse model (APPSwe, tauP301, Psen1tm1Mpm) which features am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 88 publications
2
33
0
Order By: Relevance
“…Motivation to drink can vary among individuals and drinking phenotypes may be divided into “reward-drinkers” and “relief-drinkers” (Heinz et al, 2003; Glöckner-Rist et al, 2013; Mann et al, 2018). Rates of reward-drinking and relief-drinking among the elderly are unknown; furthermore, the relationship between different drinking phenotypes and aging, as well age-related disease like AD, is unclear, with conflicting reports of negative, positive, or no effect of alcohol consumption on AD progression (Tyas, 2001; Panza et al, 2012; Ilomaki et al, 2015; Heymann et al, 2016; Xu et al, 2017; Rehm et al, 2019; Kamal et al, 2020; Barnett et al, 2022). Therefore, it is difficult to assess correlation vs. causation, as well as directionality: does AD pathology drive increased alcohol consumption, or does increased alcohol consumption impact AD pathology?…”
Section: Introductionmentioning
confidence: 99%
“…Motivation to drink can vary among individuals and drinking phenotypes may be divided into “reward-drinkers” and “relief-drinkers” (Heinz et al, 2003; Glöckner-Rist et al, 2013; Mann et al, 2018). Rates of reward-drinking and relief-drinking among the elderly are unknown; furthermore, the relationship between different drinking phenotypes and aging, as well age-related disease like AD, is unclear, with conflicting reports of negative, positive, or no effect of alcohol consumption on AD progression (Tyas, 2001; Panza et al, 2012; Ilomaki et al, 2015; Heymann et al, 2016; Xu et al, 2017; Rehm et al, 2019; Kamal et al, 2020; Barnett et al, 2022). Therefore, it is difficult to assess correlation vs. causation, as well as directionality: does AD pathology drive increased alcohol consumption, or does increased alcohol consumption impact AD pathology?…”
Section: Introductionmentioning
confidence: 99%
“…than males ( Pascual et al, 2017 ). We recently reported using a similar adolescent treatment in 3xTg-AD mice (5g/kg/d 2-days on 2-days off, P25–P55) that females, but not males, showed persistent proinflammatory gene induction along with increased AD pathology in the hippocampus in adulthood (P200), that was prevented by the anti-inflammatory compound minocycline ( Barnett et al, 2022 ). However, the question of the sex-differences in the persistence of proinflammatory signaling after ethanol during adulthood has not been rigorously assessed previously in wild-type adult rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Our P301S animals likely had tau lesions present during the latter part of the IA paradigm and at the 7-month time point used in our physiological studies. While we did not evaluate the effects of long-term ethanol consumption on tau accumulation, previous work using the triple transgenic AD mouse model (3xTg-AD), which includes a knock-in P301L tau variant along with additional AD-associated presenilin and amyloid precursor protein variants (Oddo et al, 2003), has demonstrated increased phosphorylated tau accumulation in the hippocampus, piriform cortex, medial prefrontal cortex, entorhinal cortex, and amygdala following both binge and long-term ethanol consumption (Barnett et al, 2022; Hoffman et al, 2019; Tucker et al, 2022). Future studies will need to investigate the impacts of alcohol consumption on tau accumulation in the LC itself.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy alcohol consumption throughout life may enhance the risk for developing dementia from tauopathy disorders, including AD and frontotemporal dementia (FTD) (Heymann et al, 2016; Peng et al, 2020; Rehm et al, 2019; Tyas, 2001; Wang et al, 2021). Mouse models of AD have also demonstrated increased AD-associated pathology due to alcohol consumption (Barnett et al, 2022; Hoffman et al, 2019; Tucker et al, 2022). While there appears to be a clear linkage between alcohol use, the ageing brain, and tauopathies including FTD and AD, there has been relatively little work examining the interaction of tau and alcohol in specific neural circuits.…”
Section: Introductionmentioning
confidence: 99%